Guidelines for the diagnostic cross sectional imaging and severity scoring of chronic pancreatitis - Frøkjær, Jens Brøndum; Neoptolemos, John P. (Pancreatology, 2018)
The paper presents the international guidelines for imaging evaluation of chronic pancreatitis. The following consensus was obtained: Computed tomography (CT) is often the most appropriate initial imaging modality for evaluation of patients with suspected chronic pancreatitis (CP) depicting most changes in pancreatic morphology. CT is also indicated to exclude other potential intraabdominal pathologies presenting with symptoms similar to CP. However, CT cannot exclude a diagnosis of CP nor can it be used to exclusively diagnose early or mild disease. Here magnetic resonance imaging (MRI) and MR cholangiopancreatography (MRCP) is superior and is indicated especially in patients where no specific pathological changes are seen on CT. Secretin-stimulated MRCP is more accurate than standard MRCP in the depiction of subtle ductal changes. It should be performed after a negative MRCP, when there is still clinical suspicion of CP. Endoscopic ultrasound (EUS) can also be used to diagnose parenchymal and ductal changes mainly during the early stage of the disease. No validated radiological severity scoring systems for CP are available, although a modified Cambridge Classification has been used for MRCP. There is an unmet need for development of a new and validated radiological CP severity scoring system based on imaging criteria including glandular volume loss, ductal changes, parenchymal calcifications and parenchymal fibrosis based on CT and/or MRI. Secretin-stimulated MRCP in addition, can provide assessment of exocrine function and ductal compliance. An algorithm is presented, where these imaging parameters can be incorporated together with clinical findings in the classification and severity grading of CP.
Gesehen am 13.12.2019